1974
DOI: 10.1161/01.str.5.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Unilateral Cerebral Infarction on the EEG and Behavior of the Rat

Abstract: Abstract• Anoxic ischemia with resultant unilateral cerebral infarction was produced in the rat by unilateral ligation of the external and common carotid arteries and exposure of the animal to nitrogen. EEG and behavior were studied for one month after the anoxic insult. Infarcted animals showed prominent circling, contralateral flexion postures, and absent visual and tactile placing. At the end of one month the only persistent clinical abnormality was absent contralateral tactile placing. Acutely the EEG show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In previous experiments 7 with spontaneously breathing animals, hypoxia was complicated by apnea requiring frequent resuscitations. This was eliminated in the present PYRAMIDAL TRACT RESPONSES/Su/ter et al study by mechanically ventilating curarized animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous experiments 7 with spontaneously breathing animals, hypoxia was complicated by apnea requiring frequent resuscitations. This was eliminated in the present PYRAMIDAL TRACT RESPONSES/Su/ter et al study by mechanically ventilating curarized animals.…”
Section: Discussionmentioning
confidence: 99%
“…During hypoxia EEG activity is lost rapidly within 10 to 60 seconds. 2 ' 7 In the visual system hypoxia first produces loss of synaptic activity in the occipital cortex and only later is synaptic activity impaired in the lateral geniculate body. 8 Hossmann and Sato 1 have shown that pyramidal tract responses (PTRs) persist during anoxia in the absence of spontaneous EEG activity.…”
Section: Introductionmentioning
confidence: 99%